2016
DOI: 10.3846/13923730.2015.1106578
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Influence of Nano-Reinforcement on the Mechanical Properties of Composite Materials

Abstract: The present work studies the possibility to decrease the formation of micro and nano cracks around short fibres in fibre-reinforced concrete (FRC) composite with the help of nano-reinforcement, which is carbon nanotubes, or micro reinforcement, which is carbon short fibres and nano-fillers. Tensile and bending strength of FRC depends on the spatial distribution of fibres inside a material, type of fibre and cement matrix, as well as an effective micromechanical work of each fibre while pulling out of the concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In the past, one of the main engineering challenges was the development, introduction, and mass production of efficient materials in all industrial areas. Different fiberreinforcement options are used in various fields [1][2][3][4][5], including the use of various materials and technologies [6][7][8][9]. Due to its superior physical characteristics, such as low density, thermal constancy, high strength, and modulus of elasticity, polyacrylonitrile (PAN) is a commercially important semicrystalline polymer [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, one of the main engineering challenges was the development, introduction, and mass production of efficient materials in all industrial areas. Different fiberreinforcement options are used in various fields [1][2][3][4][5], including the use of various materials and technologies [6][7][8][9]. Due to its superior physical characteristics, such as low density, thermal constancy, high strength, and modulus of elasticity, polyacrylonitrile (PAN) is a commercially important semicrystalline polymer [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some authors identified the optimal amount of combined steel microfibers and carbon nanofibers embedded in a UHPFRC providing a balanced increase in the flexural and compressive strengths [ 35 ]. Furthermore, a significant increase in the bond between cement matrix and steel microfibers is obtained in [ 36 ], via the incorporation of a small percentage of nanotubes, thus leading to a higher concrete pull-out strength. Specifically, the above-mentioned enhanced bond strength, associated with a stronger crack bridging effect in the proximity of the steel fibers, is capable to inhibit the micro-crack onset and to delay the subsequent fracture propagation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Short fibers may be used as the main or the secondary reinforcement (in combination with rebars), bearing the bending moments and the shear stresses. Several papers reported on the research into the properties of the concrete matrix successfully reinforced with various fibers made of various materials [19][20][21][22][23] and using different methods [24][25][26]. Fibers can be easily introduced into the concrete during ingredient mixing.…”
Section: Introductionmentioning
confidence: 99%